Empowering MSMEs through Sentra Produksi Bersama (SPB) to Enhance Export Product Competitiveness - Mochamad Heru Riza Chakim; Sri Rahayu; Fitra Putri Oganda; Jihan Zanubiya; Rifqa Nabila Muti; Galih Putra Cesna; Efa Ayu Nabila (ADI Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy but continues to face obstacles in meeting quality standards, technological limitations, and access to global markets. The focus of this community service program is the Karang Taruna of Kotabaru Agung Residential Area, Tangerang Regency, Banten, which possesses entrepreneurial potential that has not yet been optimally managed. The program employs a participatory method through stages of situation analysis, training, mentoring, and evaluation. It is directed toward enhancing human resource capacity through entrepreneurship, business management, and digital marketing training, while also strengthening production infrastructure with modern technologies such as vacuum frying machines, oil spinners, and slicers. The outcomes demonstrate improvements in partners’ managerial and technical skills, better product quality, and the adoption of more professional packaging standards that aligned with market demands. Furthermore, the program supports the achievement of the SDGs and Higher Education Key Performance Indicators by reinforcing collaboration among academics, communities, and external partners. In conclusion, the Sentra Produksi Bersama (SPB) model has proven effective in improving MSME competitiveness and should be further expanded through strengthened access to financing, integration into global supply chains, and the utilization of digital technologies to ensure sustainability and replication in other regions.